New multileaf collimator with a leaf width of 5 mm improves plan quality compared to 10 mm in step-and-shoot IMRT of HNC using integrated boost procedure - Zwicker, Felix; Hauswald, Henrik; Nill, Simeon; Rhein, Bernhard; Thieke, Christian; Röder, Falk; Timke, Carmen; Zabel-du Bois, Angelika; Debus, Jürgen; Huber, Peter E. (Strahlentherapie und Onkologie, 2010)
To investigate whether a new multileaf collimator with a leaf width of 5 mm (MLC-5) over the entire field size of 40 × 40 cm2 improves plan quality compared to a leaf width of 10 mm (MLC-10) in intensity-modulated radiotherapy (IMRT) with integrated boost for head and neck cancer.
Gesehen am 02.11.2023